RETRACTED: Study and analysis of existing polymer binders used in the production of wood chip materials - Jalilov Sherali; Rubidinov Shokhrukh; Gayratov Jasurbek (E3S Web of Conferences)
See the retraction notice E3S Web of Conferences 538, 00001 (2024), https://doi.org/10.1051/e3sconf/202453800001